Parental experience of change following VIPP-SD in families with preschool children with externalizing behavior: A qualitative interview study - Nina M. Lassen; Tine Steenhoff; Bryan Cleal; Amanda Frees; Mette S. Væver (PLoS ONE, 2025)
Background Insensitive parenting and ineffective disciplinary strategies are known risk factors for child externalizing behavior. The Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) has documented effect in promoting sensitive parenting, but little is known on how VIPP-SD is experienced by parents. This study explores how parents of preschool children with externalizing behaviors experience change following VIPP-SD delivered by trained childcare providers. Methods Individual qualitative semi-structured interviews were conducted with 9 mothers and 2 fathers to explore the parents’ experiences of change following the intervention. Data were analyzed using Braun and Clarke’s reflexive thematic analysis. Results Four themes were generated: 1) “All of her behavior is actually just a result of how she feels, right?”—Enhanced parental understanding, 2) Meeting the child’s needs in comfort and in play, 3) Learning to prevent and manage conflicts is essential–diverse experiences of gains and progress, 4) “I’m actually not a bad parent”–new positive perspectives. Conclusion Parents experienced an enhanced capacity to understand their child and positive development in their parenting behavior, skills and confidence as well as improvements in the parent-child relationship after receiving VIPP-SD. Findings also suggest potential areas for adaptation of VIPP-SD when intervening in families with a child exhibiting externalizing behaviors, as parental experiences of gains related to conflict management varied. Further research on this matter is recommended.